Ground‐glass burden as a biomarker in neuroendocrine cell hyperplasia of infancy. Issue 6 (6th March 2019) - Spielberg, David R.; Brody, Alan S.; Baker, Michael L.; Woods, Jason C.; Towe, Christopher T.
Abstract: Background: Neuroendocrine cell hyperplasia of infancy (NEHI) is a rare pediatric interstitial lung disease (ILD). Distinct chest computed tomography (CT) define its radiographic appearance—specifically, ground‐glass (GG) opacities most prominent in the right middle lobe (RML) and lingula. We sought to quantitatively validate this description and correlate radiologic findings with clinical presentation. Methods: Twenty‐one children with NEHI were identified retrospectively, alongside 10 age‐matched controls without lung disease. Clinical histories were reviewed for NEHI subjects. Semiautomated image analysis was used to measure lung volume and density. A patient‐specific Hounsfield unit threshold defining GG was developed to quantify GG and assess its distribution in each subject. Results: NEHI subjects had more GG than controls (37.9 ± 11.3% vs 14.0 ± 2.7%, P < 0.0001). The proportion of GG in the RML and lingula was greater in NEHI patients compared to controls (1.43 ± 0.37 vs 0.45 ± 0.21, P < 0.0001). GG preferentially involved the RML and lingula in 20/21 NEHI subjects. There was more GG distribution in NEHI subjects who were prescribed continuous oxygen compared with those using only nocturnal oxygen (45.7 ± 8.9% vs 29.3 ± 6.1%, P = 0.003). Conclusions: We confirm the previously reported finding that most patients with childhood ILD and a distinctive pattern of GG distribution on CT scan are likely to have NEHI. The amount of GG may be a biomarker for severity of respiratory disease.